CaY2Al4SiO12:Ce3+, Mn2+: a single component phosphor to produce high color rendering index WLEDs with a blue chip. Issue 34 (5th August 2021) - Zhang, Qiuhong; Li, Junhao; Jiang, Wei; Lin, Litian; Ding, Jianhong; Brik, Mikhail G.; Molokeev, Maxim S.; Ni, Haiyong; Wu, Mingmei
Abstract : Energy transfer enables the CaY2 Al4 SiO12 :Ce 3+, Mn 2+ phosphor to produce a broad band emission covering the bluish green to deep red region. A high color rendering index WLED can be obtained. Abstract : A high color rendering index white light emitting diode (WLED) is generally produced by combining yellow and red mixed phosphors on a blue chip. Herein we report a single component phosphor based on CaY2 Al4 SiO12 (CYAS) to achieve warm white light emission with a high color rendering index ( R a ), which can be up to 90.5. Ce 3+, Mn 2+ singly doped and co-doped CYAS phosphors have been synthesized by solid state reactions, respectively, for comparative investigations. The Rietveld X-ray diffraction (XRD) refinements show that the CYAS host crystallizes in a cubic structure with the Ia 3̄ d space group. The valence states of Ce and Mn inside the CYAS host have been confirmed by XPS and EPR. Ce 3+ occupies the Ca 2+ /Y 3+ site and generates a yellow emission band around 543 nm from its characteristic 5d–4f transition. Mn 2+ occupies both the dodecahedron Ca 2+ /Y 3+ and octahedral Al 3+ sites, emitting red and deep red lights at 616 nm and 750 nm, respectively. These two emission bands are attributed to the 4 T1 ( 4 G)– 6 A1 ( 6 S) transitions of Mn 2+ . Upon 460 nm light excitation, both the Ce 3+ and Mn 2+ characteristic emissions can be obtained, in which the emissions of Mn 2+ result from the occurrence of energy transfer from Ce 3+ in CYAS. All the results indicate that the prepared CYAS:Ce 3+, Mn 2+ could be a promising single component phosphor for blue chip WLEDs.